2007
DOI: 10.1111/j.1365-2893.2006.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemokines as inflammatory mediators in chronic hepatitis C virus infection

Abstract: Hepatitis C virus (HCV) is a leading cause of chronic liver disease that can progress to cirrhosis and/or hepatocellular carcinoma. Intrahepatic inflammation and liver cell injury are defining features of chronic HCV infection. Chemokines, chemotactic cytokines that attract leucocytes to inflammatory sites, may be important in the development of intrahepatic inflammation. As T-helper (Th)1 inflammatory cells, characterized by interferon (IFN)-gamma and interleukin (IL)-2 secretion, predominate in the liver dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
162
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(178 citation statements)
references
References 112 publications
7
162
0
6
Order By: Relevance
“…Thus, these chemokines have been suggested to be potential therapeutic targets in cancer, allograft rejection, diabetes, multiple sclerosis and autoimmune disorders of the thyroid (10). IP-10 has also been found to be associated with hepatic inflammation and to be a potential marker of treatment outcome (11). Previous studies have also shown that the CXCL10/IP-10 level is elevated in the sera and livers of progressed HBV carriers, and that the -1596T-201A haplotype is associated with higher CXCL10/IP-10 transcription in IFN-γ-stimulated peripheral blood mononuclear cells (5).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, these chemokines have been suggested to be potential therapeutic targets in cancer, allograft rejection, diabetes, multiple sclerosis and autoimmune disorders of the thyroid (10). IP-10 has also been found to be associated with hepatic inflammation and to be a potential marker of treatment outcome (11). Previous studies have also shown that the CXCL10/IP-10 level is elevated in the sera and livers of progressed HBV carriers, and that the -1596T-201A haplotype is associated with higher CXCL10/IP-10 transcription in IFN-γ-stimulated peripheral blood mononuclear cells (5).…”
Section: Discussionmentioning
confidence: 87%
“…Meanwhile, IP-10 has been a widely studied cytokine with respect to HCV infection. As the name suggests, it is a chemokine, inducible by IFN-γ [45] and produced by several cell types such as hepatocytes, NK cells, monocytes, and T-lymphocytes [46]. During HCV infection, hepatocytes produce IP-10 and circulating levels of IP-10 are known to be measurable during chronic HCV infection [37].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in two other studies baseline levels of IP10 were associated with a negative prognostic response to treatment with peg-IFN-and ribavirin (Butera et al, 2005;Lagging et al, 2006). Interestingly, as the CCL 3-5 are produced in the portal vascular endothelium while IP-10 is produced mainly in sinusoidal endothelium and hepatocytes surrounding lobular inflammation (Zeremski et al, 2007). Fig.…”
Section: Chemokines At Baselinementioning
confidence: 99%